“Functional upcycling” of polymer waste towards the design of new materials; Chemical Society Reviews; Vol. 52, iss. 14 - Guselnikova O. A. Olga Andreevna; Semyonov O. V. Oleg Vladimirovich; Sviridova E. V. Elizaveta Vitaljevna; Gulyaev R. O. Roman Olegovich; Gorbunova A. Alina; Kogolev D. A. Dmitry Anatoljevich; Trelin A. Andrey; Yamauchi Yu. Yusuke; Boukherroub R. Rabah; Postnikov P. S. Pavel Sergeevich (2023, 2023)
Title screen